The Study the Relevance of the Development of a Garbage Power Plant to the Large Increase in Waste Volume in Indonesia - Alim, M. Syaiful; Lastomo, Dwi; Nurbaiti, Nurbaiti; Yoesgiantoro, Donny; Laksmono, Rudy (Faculty of Advanced Technology and Multidiscipline Universitas Airlangga, 2023)
Garbage endangers the community in terms of health, the economy, and the land that is taken up. Indonesia is a country with many waste piles, but there is waste management in terms of recycling, the use of computers, and other things, even from energy sources for power plants. The Waste Power Plant (PLTSa) is an electric power plant that helps add electrical energy for the PLN to be distributed to the community. The source of combustion and the driving point for garbage power plan (PLTSa) is waste; therefore, most of these locations are located in landfills in big cities. This research article aims to strengthen the argument that the development of PLTSa can be accelerated because the increase in waste piles every year will cause unmanaged waste to also increase. The results of studies and literacy studies show that the average managed waste pile is 15,000 tons/year and still leaves 5 million tons/year of waste that is not appropriately managed; however, the PLTSa capacity is still small at 10 MWh/year. It is necessary to increase the quality of waste containers as a source of PLTSa energy to reduce the amount of unmanaged waste.